Functional elongational and adhesive strategies in the microstructured exoskeleton of the kissing bug Mepraia spinolai - Melo-Hurtado, F (ELSEVIER SCI LTD, 2026)
Adverse and unpredictable environmental conditions constrain feeding and survival in wildlife. In the kissing bug Mepraia spinolai, the abdominal exoskeleton plays a key role in sustaining the extraordinary feeding capacity of the nymphal stages. Our results show that the exoskeleton is a layered composite showing a material gradient. The stretchable capacity is attributed to micro-wrinkles and micropillars located in the exocuticle, which covers a softer and thicker endocuticle. Moreover, the epicuticle exhibits weak adhesive properties that enable the attachment of a thin granular film. This loosely adhered layer, supported by the wrinkled substrate, expands easily and prevents strong adhesion of large particles. Altogether, these findings highlight how hierarchical structural design and compositional gradients confer M. spinolai s exoskeleton with extraordinary expandability without compromising protection, offering insights into bioinspired strategies for designing multifunctional structural materials with tunable mechanical responses.